‘ELECTION’ A Bibliometric Review From 2018 - 2024 In South East Asia - Alamsyah, Anggriani (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2024)
Elections play a crucial role in democratic processes in Southeast Asia, serving as a platform for political participation and governance. Despite its significance, a comprehensive bibliometric analysis focusing on this region remains limited. This study conducts a bibliometric analysis of Scopus indexed publications on